Purification and characterization of acidophilic xylanase from Bacillus sp. with potential application as fruit juice clarifier - Chauhan, Jasmita; Bishoyi, Ashokkumar; Gohel, Rajeswaree; Sanghvi, Gaurav (Emirates Journal of Food and Agriculture, 2023)
Two bacterial isolates from the mangrove’s soil were isolated and screened for xylanase production. Screened isolates designated as AS1 and AS2 were identified by sequencing and found to be Bacillus altitudinis and Bacillus licheniformis. The highest xylanase activity recorded from Bacillus altitudinis is 82.664 units per ml and from Bacillus licheniformis is 153.59 unitsper ml at pH 4.0. Purification of the crude enzyme was done by molecular sieve chromatography and molecular weight was estimated by the SDS PAGE method. The molecular weight of xylanase was noted as 43 and 40 kDa respectively. Temperature 40°C and pH 4.0 was found to be optimum for purified xylanase enzyme. Purified xylanase was active in broad pH and temperature range. Purified xylanase activity was repressed upon incubation with FeSO4 solution. Application of purified xylanase was done in clarifying different fruit juices.The results of fruit juice clarification indicate the escalation in the sugar concentration and transparency in the juices. Percent transmittance of fruit juices showed 25.11%, 75.82%, 52.40%, 40.09%, and 30.21% for apple, orange, mousambi, pineapple, and kiwi respectively, with Bacillus altitudinis xylanase. while 44.31%, 80.12%, 72.11%, 33.00%, and 21.42 for apple, orange, mousambi, pineapple, and kiwi respectively, with Bacillus licheniformis Xylanase. The application studies show the potential of purified xylanase as a clarifier in food Industries. Keywords: Acidophiles; Xylanase; Fruit juice clarification; Profiling; Bacillus sp